Necrotizing soft tissue infections: a clinical profile - C. P., Harikrishnan; Vakayil, Happy Johny (International Surgery Journal, 2017)
Background: Necrotizing soft tissue infections (NSTIs) are a rapidly progressing fatal disorder and the prognosis of which depends on early diagnosis and management. Methods: This was a prospective observational study carried out in the surgical department of Jubilee Mission Medical College and Research Institute from August 2010 to August 2012 in 75 patients presented with NSTIs having extensive tissue necrosis. The following parameters were analyzed: demographics, infection site, laboratory findings, isolated microorganisms, antibiotics used, total hospital stays, predisposing factors, associated comorbidities and secondary management performed. Results: 75 patients with NSTIs were enrolled in this study. Youngest in this series is 3 years and oldest patient was 89 years old, with most-commonest age group being 41 to 60 years. Average age of patients is 55 years. Male: Female is in the ratio 9:1. Diabetes mellitus was seen as the common underlying disease in 20 patients. Lower limb (85%) was the most commonly affected site. Most of the patients (69) arrived with a delay in intervention of more than 3 days. Average delay in intervention from onset of symptoms of patients is 10 days. After analyzing, 26 patients were categorized in to Group 1 (survival) and the remaining 49 were into Group 2 (morbidity/mortality). In death patients Creatinine is very high 2.3 mg/dl and it is least in non-morbidity. In cases with morbidity it varies from 1.27-1.87 mg/dl. The incidence ratio of monomicrobial: polymicrobial: sterile microbial culture was 2:2:1. E. coli is the highest seen organism in monomicrobial and polymicrobial cases. Klebsiella is mostly seen in poly organism. Staphylococcus aureus is seen reasonably in polymicrobial and monomicrobial cases. Meropenem and imipenen are instituted as the most sensitive drugs with sensitivity above 90%. Most patients where managed by healing with secondary intention or split skin grafting. The average number of debridement is 1.2. The average duration of hospital stay is 26 days. 12 patients developed septicemia with multi organ dysfunction syndrome (MODS) as complications. Of these three patients survived. Mortality rate was 12%. Conclusions: NSTI is a lethal disease and early diagnosis based on high index of clinical suspicion and prompt and aggressive surgical, antibiotic and supportive therapy is essential for the better prognosis and early recovery of the disease.